Musa acuminate seed extract attenuates the risk of obesity and associated inflammation in obese mice via suppression of PPARγ and MCP-1. Issue 1 (January 2023) - Islam, Sajedul; Bhowmik, Dipty Rani; Roy, Sourav; Rahman Shuvo, Md. Sadikur; Begum, Rahima; Hasan, Maruful; Amin, Mohammad Tohidul; Ud Daula, AFM Shahid; Hossain, Mohammad Salim
Abstract: Obesity is a severe public health burden and a major component of metabolic syndrome. It is critical to identify treatment medicines for obesity and associated inflammation. We examined the anti-obesity and anti-inflammatory properties of Musa acuminate seeds methanol extract in high-fat diet-induced obesity. Changes in body weight, Lee index, fat mass accumulation, serum cholesterol, and serum triglyceride were monitored. Alteration in the expression of PPARγ, GLUT4, and MCP-1 at the transcript level in adipose tissue was also studied. After tabulation of our data, a significant reduction (p < 0.05) was recorded for body weight gain, and fat mass accumulation followed by significant changes (p < 0.05) in serum cholesterol, and serum triglyceride levels by the extract. In agreement with the biochemical data, the extract was capable enough (p < 0.05) to reduce the mRNA expression of PPARγ, and MCP-1, confirming the ability of the extract to ameliorate the risk of obesity and obesity-associated inflammation. Moreover, an in-silico study showed the high binding affinity of the reported compounds from M. acuminate like Delphinidin, Umbelliferon with COX-2, PPARγ, and MCP-1, supporting the notion of the risk-reducing potential of M.acuminate for obesity and obesity mediated inflammatory.